Multiple-Partner Fertility and Cohort Change in the Prevalence of Half-Siblings. - Amorim, Mariana; Tach, Laura M. (Demography (Springer Nature), 2019)
The transformation of the American family under the second demographic transition has created more opportunities for parents to have children with multiple partners, but data limitations have hampered prevalence estimates of multiple-partner fertility from the perspective of children. This study uses nationally representative data from the 1979 and 1997 cohorts of the National Longitudinal Surveys of Youth to examine cohort change in children's exposure to multiple-partner fertility. We find that one in five children in the 1979 cohort had at least one half-sibling by their 18th birthday, and the prevalence grew to more than one in four children by the 1997 cohort. A strong educational gradient in exposure to half-siblings persists across both cohorts, but large racial/ethnic disparities have narrowed over time. Using demographic decomposition techniques, we find that change in the racial/ethnic and socioeconomic composition of the U.S. population cannot explain the growth in exposure to half-siblings. We conclude by discussing the shifting patterns of fertility and family formation associated with sibling complexity and considering the implications for child development and social stratification.